Analysis of furnace slag in railway sub-ballast based on experimental tests and DEM simulations. (21st June 2021) - Jia, Wenli; Markine, V.L.; Jing, Guoqing
Highlights: Introducing furnace slag as railway sub-ballast. The breakage and abrasion properties are analysed. The performance of furnace slag for sub-ballast was analysed. A comparison between furnace slag with traditional sub-ballast. Abstract: Under the high requirement of ballast materials and the frequent maintenance of high-speed and heavy-haul railway, the maintenance cost and material consumption become an important problem. Several methods are used to increase the stability and service life of railway structure, also using recycled materials in ballast bed construction can be a way for railway sustainable development. Thus, an idea of using furnace slag as the sub-ballast was put forward in this research. To qualify the performance of furnace slag, a series of tests were carried out, including single particle crushing test, direct shear test, box stiffness test, and the crushed stone which is the traditional sub-ballast material was used as a comparison. In addition, the test and numerical simulation on box stiffness were carried. Results show that furnace slag has less possible to breakage and abrasion, its shear resistance is 16.46%–19.48% higher, and 20.44%–26.04% decrease in shear dilatancy. However, the stiffness for single particle shows not much difference, the box stiffness test and simulation indicated that furnace slag has a higher capacity and better elasticity. Based on that, this research provides the feasibility of using furnace slag as the sub-ballast, and it works as an environment-friendly way in railway construction.